A Community-Based Education on the Use of Medicinal Plants for Diabetes Mellitus Management among Elderly Participants at Posyandu Lansia Sadewo, Jati Village, Sidoarjo - Aida Novitasari; Irfany Nurul Hamid; Anita Joeliantina (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Diabetes mellitus is a chronic disease that requires lifelong management and often encourages patients to explore complementary therapies. Herbal remedies are frequently used alongside medical treatment, though in some cases patients reduce or discontinue prescribed medications. Limited knowledge of proper self-care and the integration of herbal therapies contributes to poor adherence and increases the risk of complications. This community service program aimed to enhance knowledge among health cadres and community members regarding the use of family medicinal plants (TOGA) as complementary therapy to support blood glucose control. The activity was conducted in RT 26 RW 06, Pondok Jati, Jati Village, Sidoarjo, focusing on communities affected by non-communicable diseases, particularly diabetes. Interventions included structured educational sessions, distribution of an educational module, and live demonstrations of herbal preparation. Effectiveness was evaluated through pre- and post-test questionnaires, assessment of program implementation, and follow-up planning. Results showed a 65% increase in participants’ knowledge of TOGA utilization for diabetes management. The coaching approach, which emphasized empowerment, emotional support, and healthy dietary practices, further demonstrated its value as a strategy for community-based diabetes prevention and management. In conclusion, integrating herbal education into community programs can substantially improve knowledge and promote complementary practices, while coaching-based interventions strengthen empowerment and encourage sustainable behavioral change.